Epidemiological trends in skin cancer - Zoe Apalla (Mattioli1885, 2017)
Skin cancer, including melanoma and non-melanoma skin cancer (NMSC), represents the most common type of malignancy in the white population. The incidence rate of melanoma is increasing worldwide, while the associated mortality remains stable, or is slightly decreasing. On the other hand, the incidence for NMSC varies widely, with the highest rates reported in Australia.